21.0k views
2 votes
Use the information provided to determine ΔH°rxn for the following reaction: ΔH°f (kJ/mol) 3 Fe2O3(s) + CO(g) → 2 Fe3O4(s) + CO2(g) ΔH°rxn = ? Fe2O3(s) -824 Fe3O4(s) -1118 CO(g) -111 CO2(g) -394

2 Answers

5 votes

Answer:

ΔH°rxn = - 47 KJ/mol

Step-by-step explanation:

  • 3 Fe2O3(s) + CO(g) → 2 Fe3O4(s) + CO2(g)

∴ ΔH°f Fe2O3(s) = - 824 KJ/mol

∴ ΔH°f Fe3O4(s) = - 1118 KJ/mol

∴ ΔH°f CO(g) = - 111 KJ/mol

∴ ΔH°f CO2(g) = - 394 KJ/mol

  • ΔH°rxn = ∑νiΔH°fi

⇒ ΔH°rxn = [ΔH°f CO2(g) + 2 ΔH°f Fe3O4(s)] - [ΔH°f CO(g) + 3 ΔH°f Fe2O3(s)]

⇒ ΔH°rxn = [- 394 KJ/mol + 2(- 1118 KJ/mol)] - [(- 111 KJ/mol) + 3(- 824 KJ/mol)

⇒ ΔH°rxn = - 2630 KJ/mol - (- 2583 KJ/mol)

⇒ ΔH°rxn = - 47 KJ/mol

User Simkusr
by
5.4k points
6 votes

Answer:

ΔH°rxn = -47 kJ

Step-by-step explanation:

Using Hess´s law for the reaction:

3 Fe2O3(s) + CO(g) → 2 Fe3O4(s) + CO2(g) ,

the ΔH°rxn will be given by the expression:

ΔH°rxn kJ = 2ΔHºf(Fe3O4) + ΔHºf(CO2) - ( 3ΔHºf(Fe2O3) + ΔHºf(CO) )

= 2(-1118) + (-394) - ( 3( -824 ) + ( -111 ) )

= - 47 kJ

User Innova
by
4.6k points